Reaction Pathway for Cocaine Hydrolase-Catalyzed Hydrolysis of (+)-Cocaine - Yao, Yuan (Theor Chem Acc, 2015)
A recently designed and discovered cocaine hydrolase (CocH), engineered from human butyrylcholinesterase (BChE), has been proven promising as a novel enzyme therapy for treatment of cocaine overdose and addiction because it is highly efficient in catalyzing hydrolysis of naturally occurring (−)-cocaine. It has been known that the CocH also has a high catalytic efficiency against (+)-cocaine, a synthetic enantiomer of cocaine. Reaction pathway and the corresponding free energy profile for the CocH-catalyzed hydrolysis of (+)-cocaine have been determined, in the present study, by performing first-principles pseudobond quantum mechanical/molecular mechanical (QM/MM)-free energy (FE) calculations. Acordingt to the QM/MM-FE results, the catalytic hydrolysis process is initiated by the nucleophilic attack on carbonyl carbon of (−)-cocaine benzoyl ester via hydroxyl oxygen of S198 side chain, and the second reaction step (i.e. dissociation of benzoyl ester) is rate-determining. This finding for CocH-catalyzed hydrolysis of (+)-cocaine is remarkably different from that for the (+)-cocaine hydrolysis catalyzed by bacterial cocaine esterase in which the first reaction step of the deacylation is associated with the highest free energy barrier (~17.9 kcal/mol). The overall free energy barrier (~16.0 kcal/mol) calculated for the acylation stage of CocH-catalyzed hydrolysis of (+)-cocaine is in good agreement with the experimental free energy barrier of ~14.5 kcal/mol derivated from the experimental kinetic data.